العدالة التنظيمية وعلاقتها بالتوافق المهني لدى عينة من أساتذة كلية العلوم الانسانية والاجتماعية بجامعة المسيلة - مزراق ايمان; اشراف: صيد حاتم (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة إلى محاولة التعرف على علاقة العدالة التنظيمية بالتوافق المهني لدى أساتذة كلية العلوم الانسانية والاجتماعية بجامعة المسيلة ، ولتحقيق أهداف الدراسة تم اعتماد على المنهج الوصفي ، ومن ثم تطبيق استمارة استبيان، وقد اجريت الدراسة على عينة مكونة من 40 استاذ واستاذة دائمين في كلية العلوم الانسانية والاجتماعية لسنة 2023-2024، تم اختيارها عن طريق عينة عشوائية،وقد اسفرت نتائج الدراسة على ما يلي: • وجود علاقة ارتباطية موجبة بين العدالة التنظيمية والتوافق المهني لدى اساتذة كلية العلوم الانسانية والاجتماعية بجامعة المسيلة • عدم وجود علاقة طردية بين بعد العدالة التوزيعية والرضا عن العمل لدى أساتذة كلية العلوم الانسانية والاجتماعية بجامعة المسيلة • عدم وجود علاقة طردية بين العدالة الاجرائية والاداء المهني لدى اساتذة كلية العلوم الانسانية والاجتماعية بجامعة المسيلة • عدم وجود علاقة طردية بين العدالة التعاملية والاستقرار المهني لدى اساتذة كلية العلوم الانسانية والاجتماعية بجامعة المسيلة Abstract:_ The study aimed to explore the relationship between organizational justice and professional adjustment among professors in the Faculty of Humanities and Social Sciences at the University of M'sila. To achieve the study's objectives, a descriptive approach was employed, and a questionnaire was used. The study was conducted on a sample of 40 permanent professors in the Faculty of Humanities and Social Sciences for the academic year 2023-2024. The sample was selected randomly. The results of the study are as follows: - There is a positive correlation between organizational justice and professional adjustment among professors in the Faculty of Humanities and Social Sciences at the University of M'sila. - There is no direct relationship between distributive justice and job satisfaction among professors in the Faculty of Humanities and Social Sciences at the University of M'sila. - There is no direct relationship between procedural justice and professional performance among professors in the Faculty of Humanities and Social Sciences at the University of M'sila. - There is no direct relationship between interactional justice and career stability among professors in the Faculty of Humanities and Social Sciences at the University of M'sila